Antibodies against neo‐epitope of microbial and human transglutaminase complexes as biomarkers of childhood celiac disease. (11th November 2019) - Agardh, D.; Matthias, T.; Wusterhausen, P.; Neidhöfer, S.; Heller, A.; Lerner, A.
Summary: Tissue transglutaminase (tTG) and microbial transglutaminase (mTG) cross‐link gliadins to form complexes that expose immunogenic neo‐epitopes to produce tTG and mTG‐neo‐epitope antibodies. The aim of this study was to test the diagnostic performance of antibodies against non‐complexed and complexed forms of transglutaminases, to correlate their activities to the intestinal damage and to explore age group dependency in celiac disease (CD). A total of 296 children with untreated CD and 215 non‐celiac disease controls were checked by in‐house enzyme‐linked immunosorbent assays detecting immunoglobulin (Ig)A, IgG or combined detection of IgA and IgG (check) against tTG, AESKULISA ® tTG New Generation (tTG‐neo) and mTG‐neo (RUO), IgA and IgG antibodies against deamidated gliadin peptide (DGP) and human IgA anti‐endomysium antibodies (EMA) using AESKUSLIDES ® EMA. Intestinal pathology was graded according the revised Marsh criteria, and age dependencies of the antibody activities were analysed. Using cut‐offs estimated from receiver operating characteristic (ROC) curves, the highest area under curve (AUC) of the TG assays was 0·963 for tTG‐neo check, followed by tTG check (0·962) when the diagnosis was based on enteric mucosal histology. tTG‐neo check was the most effective to reflect the intestinal abnormalities in CD ( r  = 0·795, P  < 0·0001). High levels of anti‐mTG‐neo IgG and anti‐tTG‐neo IgG appeared in the earlier age groups, as compared to anti‐tTG IgG ( P  < 0·001). Considering antibody diagnostic performance based on AUC, enteric damage reflection and predictability at an early age, the anti‐neo tTG check was the most effective diagnostic biomarker for pediatric CD. The mTG neo check might represent a new marker for CD screening, diagnosis and predictability. Abstract : Back to back comparison of 10 various, celiac disease associated antibody were checked in 296 children with untreated CD compared to 215 non‐celiac disease controls.Considering antibodies' diagnostic performances based on AUC, enteric damage reflection and predictability at an early age, the anti‐neo tTG check was the best diagnostic biomarker for pediatric CD.The mTG neo Check might represent a new marker for CD screening, diagnosis and predictability.